Amplitude analysis and branching fraction measurement of the Cabibbo-favored decay D + → K − π + π + π 0 - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Journal of High Energy Physics)
Abstract An amplitude analysis of the Cabibbo-favored decay D + → K − π + π + π 0 is performed, using 7.93 fb −1 of e + e − collision data collected with the BESIII detector at the center-of-mass energy of 3.773 GeV. The branching fractions of the intermediate processes are measured, with the dominant contribution D + → K ¯ ∗ 892 0 ρ 770 + $$ D^{+}→ {\overline{K}}^{* }{(892)}^0ρ {(770)}^{+} $$ observed to have a branching fraction of (4.35 ± 0.07stat. ± 0.17syst. )%. With the detection efficiency derived from the amplitude analysis, the absolute branching fraction of D + → K − π + π + π 0 is measured to be (6.35 ± 0.04stat. ± 0.07syst. )%.